Pengaruh Gamification Terhadap Customer Engagement pada Pengguna Aplikasi Gojek dengan Perceived Enjoyment Sebagai Variabel Mediasi - Widi Dewi Ruspitasari (Jurnal Manajemen dan Profesional, 2026)
This study examines the relationship between gamification and customer engagement with perceived enjoyment as a mediating variable. A quantitative survey was conducted on 75 users of the Gojek application in Malang City, analyzed using PLS-SEM. The findings indicate that gamification does not directly influence customer engagement, but significantly affects perceived enjoyment. In turn, perceived enjoyment positively influences customer engagement and fully mediates the relationship between gamification and engagement. These results suggest that user engagement is driven more by emotional experience than by gamification features alone, emphasizing the importance of enjoyable user interactions in digital platforms